Metal–salen molecular cages as efficient and recyclable heterogeneous catalysts for cycloaddition of CO(2) with epoxides under ambient conditions - Ng, Chee Koon (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
A salen based molecular cage, salen@cage, was synthesized and complexed with Co and Al to yield metal–salen molecular cages, Co(ii)@cage, Co(iii)@cage and Al(iii)@cage. These cages were demonstrated to be efficient heterogeneous catalysts for the cycloaddition of CO(2) with styrene oxide, achieving full conversion at 25 °C and 1 atm CO(2). Good to excellent yields of various cyclic carbonates were also achieved under mild conditions. Al(iii)@cage can be reused up to five times without any significant loss of its high catalytic activity. The capability to access a variety of heterogeneous organometallic catalysts with salen@cage offers new prospects for practical CO(2) utilization and chemical manufacturing.